Manifest and latent social groups: Phenomenon, evolution, determinants. Part 1 - Vladimir A. Tolochek (Saratov State University, 2022)
Objective: to study the features of the social micro- and meso-environment as potential conditions for the formation, functioning and evolution of latent social groups. Hypotheses: 1. Various conditions of the social environment are not regarded as equivalent by people (persons of different genders, ages, working in different fields of activity, having different social experience, etc.). 2. The conditions of the social environment have different subjective significance for people and collectively represent relatively autonomous and closed social spaces. Methods: historical and theoretical analysis, empirical research (questionnaire), multidimensional methods of parametric statistics. According to the author's methodology (questionnaire "Dynamics of professional life style" - DPLS), respondents assessed the role of social environment conditions as "factors of professionalism", the dynamics of their professionalism from 20 to 65 years (retrospectively to the current age and prospectively - predicting the dynamics of subsequent evolution); their socio-demographic and official characteristics were also recorded. 482 employees, men and women aged 30-50 were interviewed (132 civil servants, 129 engineers and heads of departments of industrial enterprises, 221 managers). The results of the empirical study confirm the working hypotheses. Groups of conditions of different social spaces, conventionally called "Relatives", "Inter-personal relationships", "Family environment", "Work environment", "Meso-environment", act as dominant or subdominant spheres of human activity, predetermining many differences between them. In the process of socialization, people form peculiar stable and universal mechanisms of activating and translating social experience; the lack of such experience often contributes to a person's being less open and receptive to other conditions of the social micro- and meso-environment, to their being less socially successful. Briefly, the description and study of latent social groups is relevant since it helps to identify "subtle" mechanisms of self-organization of people into social communities.